The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15585/mmwr.rr6702a1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Pertussis, Tetanus, and Diphtheria with Vaccines in the United States: Recommendations of the Advisory Committee on Immunization Practices (ACIP)

Abstract: SummaryThis report compiles and summarizes all recommendations from CDC's Advisory Committee on Immunization Practices (ACIP) regarding prevention and control of tetanus, diphtheria, and pertussis in the United States. As a comprehensive summary of previously published recommendations, this report does not contain any new recommendations and replaces all previously published reports and policy notes; it is intended for use by clinicians and public health providers as a resource. ACIP recommends routine vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
188
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(225 citation statements)
references
References 242 publications
1
188
0
2
Order By: Relevance
“…A large British retrospective cohort study using primary care data demonstrated that the benefit of passive maternal immunity did not persist beyond the third dose of primary immunisation in the infant 79. Guidelines from Public Health England26 and Centers for Disease Control and Prevention84 recommend vaccination at 16-32 weeks and 27-36 weeks of gestation respectively. Immunisation in the second trimester may be preferred as it can protect preterm infants, allow more time for maternal antibody transfer, and can logistically be combined with a routine antenatal check 858687.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
See 1 more Smart Citation
“…A large British retrospective cohort study using primary care data demonstrated that the benefit of passive maternal immunity did not persist beyond the third dose of primary immunisation in the infant 79. Guidelines from Public Health England26 and Centers for Disease Control and Prevention84 recommend vaccination at 16-32 weeks and 27-36 weeks of gestation respectively. Immunisation in the second trimester may be preferred as it can protect preterm infants, allow more time for maternal antibody transfer, and can logistically be combined with a routine antenatal check 858687.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
“…An alternative strategy, called “cocooning,” is thought to prevent pertussis indirectly by vaccination of household adolescent and adult family members who may be a source of infection for infants 84. The results have been mixed and do not support the universal implementation of cocooning 93949596.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
“…Due to widespread vaccination, tetanus infection is rare in high‐income countries. Older adults, however, have a relatively higher incidence of tetanus and also have a higher mortality rate if they are unfortunate enough to become infected . Between 2001 and 2008 in the United States, only 56.9% of those aged 65 years or older had received a tetanus‐containing vaccine within the recommended 10‐year interval for vaccination .…”
Section: Recommended Vaccinations For Older Adultsmentioning
confidence: 99%
“…Both Td and Tdap vaccines are contraindicated when there is a history of a severe allergic reaction following a prior tetanus vaccine . The Tdap vaccine is also contraindicated if a patient who received a prior dose of Tdap had encephalopathy, not attributable to another etiology, within 7 days of the vaccine being administered . Because this encephalopathy warning is related only to the pertussis component of the vaccine, these patients may receive Td instead .…”
Section: Recommended Vaccinations For Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation